Didactic Transposition: Exploring Knowledge To Be Taught In Ḥiwār Learning Materials For Grade 5th - Meisa Yasmin Nuha; Asep Sopian; Shofa Musthafa Khalid; Hikmah Maulani; Muhammad Zidan Dzulfikar (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
Teaching ḥiwar in elementary schools necessitates the transformation of curriculum content into contextually relevant and teachable materials. However, many educators tend to rely exclusively on textbooks, resulting in a disconnect between curriculum objectives and classroom practices. This study investigates the process of didactic transposition at the knowledge level in fifth-grade Arabic ḥiwar lessons, emphasizing how teachers adapt curriculum guidelines into practical learning resources. Utilizing a qualitative phenomenological approach, data were gathered through document analysis of curriculum and teaching modules, complemented by unstructured interviews with an Arabic language teacher. A praxeological study served as a framework for document analysis. The findings indicate that while the teaching modules formally align with curriculum objectives, they are seldom utilized as effective teaching tools. Educators often depend on textbooks, overlooking contextual scaffolding and systematic strategies, which leads to fragmented material delivery. This disconnect hampers students' communication skills and diminishes the effectiveness of the ḥiwar method in enhancing speaking abilities. This study underscores the necessity for dynamic teaching modules that incorporate explicit learning indicators, contextual materials, and clear instructional techniques. Strengthening the alignment between curriculum, modules, and classroom practices can mitigate didactic misalignment and enhance learning outcomes. Future research should investigate technology-based and interactive resources to optimize the transposition of didactic learning in Arabic ḥiwār. Abstrak Mengajarkan ḥiwār di sekolah dasar memerlukan transformasi konten kurikulum menjadi materi yang bermakna secara kontekstual dan dapat diajarkan. Namun, banyak guru hanya mengandalkan buku teks, sehingga menciptakan kesenjangan antara tujuan kurikulum dan praktik kelas. Studi ini meneliti proses transposisi didaktik pada tahap pengetahuan yang akan diajarkan dalam pelajaran ḥiwār bahasa Arab kelas lima, dengan fokus pada bagaimana guru mengadaptasi pedoman kurikulum menjadi materi pembelajaran praktis. Dengan menggunakan pendekatan fenomenologi kualitatif, data dikumpulkan melalui analisis dokumen kurikulum dan modul pengajaran, serta wawancara tidak terstruktur dengan seorang guru bahasa Arab yang selanjutnya dilakukan kajian praxeology sebagai alat untuk analisis dokumen. Temuan ini mengungkapkan bahwa meskipun modul pengajaran secara formal mencerminkan tujuan kurikulum, modul tersebut jarang diterapkan sebagai alat pengajaran fungsional. Guru cenderung bergantung pada buku teks, mengabaikan perancah kontekstual dan strategi sistematis, yang mengakibatkan penyampaian materi terfragmentasi. Ketidaksesuaian ini membatasi kemampuan komunikasi siswa dan mengurangi efektivitas metode ḥiwār dalam mengembangkan keterampilan berbicara. Studi ini menyoroti perlunya modul pengajaran dinamis yang mengintegrasikan indikator pembelajaran yang eksplisit, materi kontekstual, dan teknik pengajaran yang jelas. Memperkuat keselarasan antara kurikulum, modul, dan praktik di kelas dapat mengurangi kesenjangan didaktik dan meningkatkan hasil pembelajaran. Penelitian di masa mendatang sebaiknya mengeksplorasi sumber daya berbasis teknologi dan interaktif untuk mengoptimalkan transposisi didaktik pembelajaran ḥiwār bahasa Arab.